PERLINDUNGAN HAK PENYANDANG DISABILITAS DALAM MEMPEROLEH PENYEDIAAN AKSESIBILITAS SEBAGAI WISATAWAN DI LOKASI WISATA - Cynthia Rahmawati (2021)
Tourism areas currently still do not fulfill the rights of persons with disabilities as tourists as regulated in Article 21 of Law Number 10 of 2009 concerning Tourism, where tourists with physical limitations, children, and the elderly are entitled to special facilities according to their needs. Article 16 letter C of the Law on Persons with Disabilities Number 8 of 2016 also regulates the rights of persons with disabilities as tourists, namely, getting easy access, treatment, and proper accommodation according to their needs as tourists. Problem formulation: (1) How is the protection of the rights of persons with disabilities in obtaining the provision of accessibility as tourists at tourist sites (2) How is the protection of the rights of persons with disabilities in obtaining the provision of accessibility as tourists at tourist sites? This study uses a writing method called the library method, in which the author collects several libraries such as books, journals, laws and others to be studied and used in this study. The protection of rights for persons with disabilities at tourist sites has not been implemented in its implementation as stipulated in Law No. 10 of 2009 and Law No. 8 of 2016. Government accountability in providing accessibility for disabled tourists at tourist sites already exists and strictly provides sanctions for the violators, but its current implementation is still not effective and has not been implemented properly.